Clinical efficacy comparison of internal fixation of locking compression plate and cannulated screw in treatment of elderly femoral neck fractures—a retrospective study - Sun, Fei; Sun, Yu; Li, Wei; Tang, Zhi; Liu, Enxu; Li, Zhaoyong; Yang, Shaofeng (Frontiers in Surgery, 2025)
ObjectiveTo explore the clinical efficacy of internal fixation of locking compression plate and Cannulated Screw in treatment of elderly femoral neck fractures.Methods175 patients with femoral neck fractures admitted to our hospital from January 2022 to December 2022 were enrolled in the study. 93 cases in the control group were treated with Cannulated Screw internal fixation, and 82 cases in the observation group were treated with locking plate internal fixation. The control group was treated with cannulated screw internal fixation, while the observation group was treated with locking compression plate internal fixation.ResultsCompared with the control group, the observation group had a significantly shorter time for partial weight-bearing exercise, with a statistically significant difference (p < 0.05), and a significantly lower incidence of postoperative complications, with a statistically significant difference (p < 0.05). The ROM of hip extension-flexion at 1 month and 6 months after operation and the ROM of hip internal rotation-external rotation at 1 month after operation in the observation group were significantly higher than those in the control group, and the differences were statistically significant (P < 0.01). The VAS score of the observation group was significantly lower than that of the control group at 1 month after operation, and the difference was statistically significant (P < 0.01).ConclusionBoth locking compression plate internal fixation and cannulated screw internal fixation are effective in the treatment of elderly femoral neck fractures. Compared with cannulated screw internal fixation, locking compression plate internal fixation helps patients to engage in early functional exercise and has a lower incidence of postoperative complications.